Risk-taking on Behalf of Others - Kristoffer W. Eriksen; Ola Kvaløy; Miguel Luzuriaga (Center for Economic Studies and ifo Institute (CESifo), 2017)
We present an experimental study on how people take risk on behalf of others. We use three different elicitation methods, and study how each subject makes decisions both on behalf of own money and on behalf of another individual's money. We find a weak tendency of lower risk-taking with others' money compared to own money. However, subjects believe that other participants take more risk with other people's money than with their own. At the same time, subjects on average think that others are more risk averse than themselves. The data also reveals that subjects are quite inconsistent when making risk decisions on behalf of others, indicating random behavior. A large majority of subjects alternates between taking more risk, less risk or the same amount of risk with other people's money compared to own money.
Keywords: 330; risk-taking; other people's money; beliefs; preferences; experiment